A comparative study of Reynolds-averaged Navier-stokes and semi-empirical thermal solutions of a gas turbine nozzle guide vane - De Kock, Daniel Johannes (University of Pretoria, 2013)
Dissertation (MEng)--University of Pretoria, 2009.